Sociality and interaction envelope organize visual action representations - Leyla Tarhan (Nature Portfolio, 2020)
How is action perception organized in the brain? Here, the authors report evidence for five networks tuned to actions’ social content and the scale of their effect on the world and propose that sociality and interaction envelope are organizing dimensions of visual action representation.